Potential impact of 5 years of ivermectin mass drug administration on malaria outcomes in high burden countries. Issue 11 (11th November 2021) - Marathe, Achla; Shi, Ruoding; Mendez-Lopez, Ana; Hu, Zhihao; Lewis, Bryan; Rabinovich, Regina; Chaccour, Carlos J; Rist, Cassidy
Abstract : Introduction: The global progress against malaria has slowed significantly since 2017. As the current malaria control tools seem insufficient to get the trend back on track, several clinical trials are investigating ivermectin mass drug administration (iMDA) as a potential additional vector control tool; however, the health impacts and cost-effectiveness of this new strategy remain unclear. Methods: We developed an analytical tool based on a full factorial experimental design to assess the potential impact of iMDA in nine high burden sub-Saharan African countries. The simulated iMDA regimen was assumed to be delivered monthly to the targeted population for 3 months each year from 2023 to 2027. A broad set of parameters of ivermectin efficacy, uptake levels and global intervention scenarios were used to predict averted malaria cases and deaths. We then explored the potential averted treatment costs, expected implementation costs and cost-effectiveness ratios under different scenarios. Results: In the scenario where coverage of malaria interventions was maintained at 2018 levels, we found that iMDA in these nine countries has the potential to reverse the predicted growth of malaria burden by averting 20–50 million cases and 36 000–90 000 deaths with an assumed efficacy of 20%. If iMDA has an efficacy of 40%, we predict between 40–99 million cases and 73 000–179 000 deaths will be averted with an estimated net cost per case averted between US2 and US7, and net cost per death averted between US1460 and US4374. Conclusion: This study measures the potential of iMDA to reverse the increasing number of malaria cases for several sub-Saharan African countries. With additional efficacy information from ongoing clinical trials and country-level modifications, our analytical tool can help determine the appropriate uptake strategies of iMDA by calculating potential marginal gains and costs under different scenarios.